Long-term reoperation rates and causes for reoperations following lumbar microendoscopic discectomy and decompression: 10-year follow-up. (January 2022) - Aihara, Takato; Kojima, Atsushi; Urushibara, Makoto; Endo, Kenji; Sawaji, Yasunobu; Suzuki, Hidekazu; Nishimura, Hirosuke; Murata, Kazuma; Konishi, Takamitsu; Yamamoto, Kengo
Highlights: We examined the reoperation cases at 10 years after the microendoscopic surgeries. The 10-year reoperation rate for all patients combined was 22.1% (67/303). That of those who underwent repeat operations in the same segment was 16.5% (50/303). That of those who underwent repeat operations at different lumbar levels was 5.61%. We believe that understanding and preventing these problems is essential. Abstract: Objective: To investigate the 10-year rates and causes of reoperations following lumbar microendoscopic discectomy for disc herniation (MEDH) and microendoscopic decompression for spinal stenosis (MEDS), as well as to define the reoperations at index and different lumbar levels. Methods: Between June 2005 and May 2011, the same surgeon had been using MEDH and/or MEDS on 355 consecutive patients. The follow-up rate was 88.3%. The causes and rates of reoperations (RORs) were determined at 10 years after the initial operations. Results: The 10-year reoperation rate for all patients combined was 22.1% (67/303). The 10-year reoperation rate for all cases that underwent repeat operations in the same segment was 16.5% (50/303); the most frequent reason for reoperation (FRR) was recurrence of disc herniation (ROR, 25/251 = 9.96%), the second FRR was an increase of postoperative spondylolisthesis and/or instability (ROR, 8/303 = 2.64%), and the third FRR was surgical site infection (ROR, 5/303 = 1.65%). Ten-year reoperation rate for all cases that underwent repeat operation at different lumbar levels was 5.61% (17/303); the most FRR was new disc herniation at another lumbar level (ROR, 10/303 = 3.30%), the second FRR was residual segmental stenosis (ROR, 4/303 = 1.32%), and the third FRR was new segmental stenosis at other lumbar levels (ROR, 2/303 = 0.66%). Conclusions: Three-fourths of all repeat operations were conducted in the same segment and one-fourth were performed at different lumbar levels. We believe that it is important to understand and prevent related problems.